2021
DOI: 10.3390/ijerph182312820
|View full text |Cite
|
Sign up to set email alerts
|

Eating Behaviors among Online Learning Undergraduates during the COVID-19 Pandemic

Abstract: The outbreak of Coronavirus Disease-2019 (COVID-19) has upended education systems. The pandemic switched traditional face-to-face classes to online classes. Poor eating behaviors in undergraduate students’ lives may affect the well-being of their later stages of life. This study aimed to investigate the eating behaviors among online learning undergraduates during the COVID-19 pandemic. A total of 122 students were recruited. The results revealed more than half of the respondents (52.46%) skipped meals. Breakfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
2
10
2
Order By: Relevance
“…Argun et al stated that adults skip breakfast more frequently than other main meals because of lack of time, waking up late, and fatigue [24]. These results are similar to previous studies demonstrating that more than half of the surveyed respondents had meal skipping behavior as undergraduate students who studied online during the COVID-19 pandemic [18]. Under the lockdown, the reason behind the meal skipping behavior of students may be attributed to the low accessibility of food purchased from physical stores [25].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Argun et al stated that adults skip breakfast more frequently than other main meals because of lack of time, waking up late, and fatigue [24]. These results are similar to previous studies demonstrating that more than half of the surveyed respondents had meal skipping behavior as undergraduate students who studied online during the COVID-19 pandemic [18]. Under the lockdown, the reason behind the meal skipping behavior of students may be attributed to the low accessibility of food purchased from physical stores [25].…”
Section: Discussionsupporting
confidence: 70%
“…Online learning platforms have also increased the duration of computer, tablet, and smartphone usage, the study load and volume of tasks and assignments, leading to lack of sleep, and destructive eating behaviors [15,16]. Moreover, online learning during the COVID-19 pandemic resulted in changes in food intake and lifestyle habits, including increased consumption of unhealthy diets such as sugary beverages, snacks, and sweets and decreased physical activity and exercise [17][18][19]. Furthermore, it has been observed that online learning university students consumed snacks and skipped breakfast during the pandemic [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This causes unprecedented disruption to all sectors. In the education sector, students were instructed to stay at home, and the process of teaching and learning switched to virtual mode [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…General dietary habits and physical activity are also among the lifestyle factors that have changed in the COVID-19 pandemic [4,5]. In particular, the fact that individuals spend more time at home with media and social media tools has led to an increase in sedentary time [6].…”
Section: Introductionmentioning
confidence: 99%